PENGELOLAAN MGMP DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU SENI BUDAYA SMA DI KOTA CIMAHI - Nina Irnawati, - (2017)
This research deals with the management of MGMP in improving the professional competence of high school culture art teacher in cimahi city. Research focus describes the reality of professional competence; MGMP cultural arts programs; Inhibiting factors and finding solutions to overcome barriers to implementation of programs and activities to improve teacher professional competence. Research results show (1) the reality of professional competence mastery is optimal; The competence of interaction and social communication is less than optimal; Personality competence is optimal; Learning competencies are optimal; (2) four general program categories, namely: seminars and workshops, core programs are routine, namely: syllabus workshops and RPP art of high school culture; Preparation of student learning outcomes; Core development programs, namely; MGMP website development of high school culture art; Publishing journals and bulletins; Training on cultural and artistic learning innovation; Publishing textbooks on art and culture materials and training in scientific writing; Supporting programs, ie, joint business management training and secretarial pioneering. Four obstacles; Namely, human resources; facilities and infrastructure; financing; And coordination. Solutions to problem solving, namely to improve human resources by way of mindset training on all members, innovation-oriented leadership; Training of learning devices; And build a positive personality collectively; Secretarial room leasing; Procurement of office equipment; Thrifty block grand funds; Empowering member dues system; Cooperative joint venture; Synchronize regular meetings; Improve relationships and reporting system of activities and implement SOP according to its allocation. Penelitian ini berkenaan dengan Pengelolaan MGMP dalam Meningkatkan Kompetensi Profesional Guru Seni Budaya SMA di Kota Cimahi. Fokus penelitian mendeskripsikan realitas kompetensi profesional; program-program MGMP Seni budaya; faktor-faktor penghambat dan menemukan solusi mengatasi hambatan pelaksanaan program dan kegiatan peningkatan kompetensi profesional guru. Hasil penelitian menunjukkan (1) Realitas kompetensi profesional penguasaan emosi cukup optimal; kompetensi interaksi dan komunikasi sosial kurang optimal; kompetensi kepribadian cukup optimal; kompetensi pembelajaran sudah optimal; (2) Empat kategori program umumnya, yakni: seminar dan lokakarya, Program inti bersifat rutin, yakni: workshop silabus dan RPP seni budaya SMA; penyusunan laporan hasil belajar siswa; Program inti pengembangan, yakni; pengembangan website MGMP seni budaya SMA; penerbitan jurnal dan buletin; pelatihan inovasi pembelajaran seni budaya; penerbitan buku ajar materi seni budaya dan pelatihan penulisan karya ilmiah; Program penunjang, yakni, pelatihan manajeman usaha bersama dan perintisan seketariat. Empat faktor hambatan yakni: SDM; sarana dan prasarana; pembiayaan; dan koordinasi. Solusi pemecahan masalahnya, yakni meningkatkan SDM dengan cara pelatihan mindset pada seluruh anggota, kepemimpinan yang berorientasi inovasi; pelatihan perangkat pembelajaran; dan membangun kepribadian positif secara kolektif; penyewaan ruang sekretariat; pengadaan peralatan kantor; berhemat dana block grand; memberdayakan sistem iuran anggota; usaha bersama kooperasi; mengintensifkan pertemuan rutin; meningkatkan hubungan dan sistem pelaporan kegiatan dan melaksanakan SOP sesuai peruntukannya.----